AAV viral vectors as therapeutic interventions for inherited or non-inherited cardiac disorders: current aspects and future prospects - Kumar, Vivek; Kalishwaralal, Kalimuthu; Chauhan, Charu; Singh, Gurpal; Barnwal, Ravi Pratap; Sharma, Sachin (Frontiers in Medicine, 2025)
Ischemic and non-ischemic cardiac diseases including arrhythmogenic cardiomyopathy and myocardial infarction, remain one of the leading causes of death worldwide despite significant advances in cardiovascular therapeutics. Current treatment strategies such as β-blockers, angiotensin-converting-enzyme inhibitors, and cardiac surgical interventions that include implantations of pacemakers and cardioverter-defibrillators are effective but often associated with serious side effects. In recent years, multiple cell-based therapies have emerged, aiming either to regeneration of myocardial or myofascial tissues or to correct defective gene using gene-transfer tools. Adeno-associated virus (AAVs), initially identified as contaminants of adeno-virus preparations, have since become one of the most important viral vectors for gene-transfer, especially in mammalian cells. This review analyzes and summarizes various AAV serotypes utilized in gene therapy programs for preclinical and clinical assays for cardiac disease.